Non genetic factors influencing fertility problems in Murrah buffaloes - M, MANOJ; GUPTA, A K; MOHANTY, T K; ASLAM, M K MUHAMMAD; CHAKRAVARTY, A K; SINGH, A; MALHOTRA, R; GANDHI, R S (The Indian Journal of Animal Sciences, 2015)
The data on 2449 reproduction records of Murrah buffaloes were analysed using SAS to study the effect of various non genetic factors on the incidence of fertility problems (repeat breeding, true anoestrus and anoestrus due to persistent corpus luteum). The association between non-genetic factors and fertility problems were analysed using Chi squares method. To study the effect of these independent variables simultaneously, multiple logistic regression method was used. Overall fertility problems and true anoestrus were significantly (p